Thin film flow and heat transfer on an unsteady stretching sheet with internal heating - Raziana Che Aziz; I. , Hashim; Alomari, A.K. (Springer Netherlands, 2009)
This research studied the influence of internal heat generation on flow and heat transfer in a thin liquid film on an unsteady stretching sheet. The velocity and temperature fields were solved using the Homotopy Analysis Method (HAM), taking a general surface temperature into consideration. The analytical series solution are presented and the numerical results obtained are tabulated. The effects of unsteadiness parameter, Prandtl number and temperature-dependent parameter in this study are discussed and presented graphically via the velocity and temperature profiles. (Authors' abstract)